Improving attitudes toward mathematics and teacher self-efficacy through Service-Learning and Gamification - Santaolalla Pascual, Elsa; Martín Carrasquilla, Olga; Urosa Sanz , Belén (Revista Complutense de Educación, 2025)
INTRODUCTION. Attitudes towards mathematics and teacher self-efficacy have a great influence on the involvement and academic performance of students, which is why it is important that teacher training programmes implement methodologies that favour their development in preservice teachers. METHODS. The aim of this study is to check whether the use of active methodologies in initial teacher training strengthens: a) attitudes towards mathematics, b) general teacher self-efficacy in mathematics and c) self-efficacy for the design and development of mathematics teaching materials. Specifically, service-learning (SL) and gamification have been used since both give importance to the affective aspects involved in the teaching and learning process. Research has been carried out for two consecutive years, with 120 students who have taken the subject of Didactics of Mathematics of the Degree in Primary Education with two different innovative methodological approaches. In the academic year 2021/22 through Gamification (N = 64) and in the academic year 2022/23 with SL (N = 56). The study was conducted through a quasi-experimental design with pre/post-treatment measures of the key variables. RESULTS. The results show a statistically significant improvement (p<.001) in the three variables and also reveal statistically significant differences (p<.05) in the attitudes towards mathematics in favour of the students who participated in the SL projects with respect to the gamification projects. DISCUSSION. The importance of using active methodologies, in particular SL and Gamification, in initial teacher training to strengthen attitudes towards mathematics and teaching self-efficacy is evidenced, and the initiatives that are being carried out to institutionalise SL in Higher Education are reinforced.